Smart or Selfish - When Smart Guys Finish Nice - Johannes Lohse (University of Heidelberg, Department of Economics, 2014)
In three different variants of an one-shot public good game I analyze the relationship between cooperation and cognitive abilities, assessed through the cognitive reflection test (CRT). In a between-subjects design, the baseline case is contrasted with two treatment conditions that allow to control for two potentially moderating factors: By employing a test for the presence of confusion, the first condition scrutinizes whether higher cognitive abilities are correlated with cooperation proper or simply grant a better understanding of the incentive structure. The second condition explores the proposition that the link between cognitive abilities and cooperation could depend on the complexity of the decision situation. To exogenously create a cognitively more demanding choice setting, subjects had to decide under time pressure. I find a strong and positive relationship between CRT-scores and cooperation, that is not driven by confusion. Time pressure has a strongly moderating effect on this relationship.
urn:nbn:de:bsz:16-heidok-177482
Keywords: 330; Cooperation; Cognitive Abilities; Confusion; Public Goods; Dual Process Theories